PanarinV., HumeniukI., KindrachukV. , Tisov O. Investigation of tribotechnical properties of electrosparc coatings made of eutectic alloy based on steel 12Х18Н10 - Панарін, В. Є.; Гуменюк, І. А.; Кіндрачук, М. В.; Тісов, О. В. (Problems of Tribology, 2018)
In current work we have investigated an urgent problem of managing tribologial properties of steel based composite coating. As a material of the coating we used an eutectic alloy with chromium and titanium diborides as strengthening phases. The chemical composition of matrix material was a composition of stainless steel 12X18H9. IA substrate material is a steel 12Х18Н10Т. For coating deposition we used an electrospark method in protective argon atmosphere, which allows to obtain coating material in quasistable condition. As a result of equilibrium cooling the coating has s following structure: dendritic crystals of diborides with spaces filled with steel matrix. These strengthening crystals bear the major amount of friction load. Increasing the cooling rate of molten material the coating structure changes (after some critical cooling rate) – it turns to a fine strengthening crystals embedded into steel matrix. We call this a fine phase conglomeration. Reheating the coating allows tu turn this conglomeration to more (or to equilibrium) thermodynamically stable state (coating annealing). For tribological testing we used a wear test facility M22-P which utilizes a shaft - bush test specimens layout. A counterspecimen (shaft specimen) material is steel 45 hardened to 45 HRC. We have tested three series of specimens without any treatment (is as deposited condition), і після відпалу – 15 і 45 хв. It was proved, that coating reheating changes hardness, corrosion resistance, wear resistance. By selecting heating temperature and annealing duration it is possible to change tribological behavior of material. This allows to select a definite set of properties, which are required for particular application.